Length-Weight Relationship in Salmostoma navacula and Channa muralius Godavari River at Kaigaon Toka, Dist. Aurangabad (M.S.) India - Shinde S.E.; More P.R, Rathod S.R., (Recent Research in Science and Technology, 2011)
The length-weight relationship of Salmostoma navacula and Channa muralius were studied Godavari River at Kaigaon Toka from January 2010 to December 2010. The exponential value of fishes indicates allometric growth pattern in the natural habitat. The logarithmatic regression equation obtained in Salmostoma navacula was log W = -0.531+1.70 LogL and in Channa muralius was Log W = -0.067+1.45 LogL. The coefficient of correlation in Salmostoma navacula was r = 0.711 and in Channa muralius was r = 0.967. Which shows the correlation factor revealed positive correlation between length and weight.